Фруктозоиндуцированная токсичность: рациональность применения фитосбора - Сукиасян, Л. М. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Հոդվածը ժամանակակից բժշկության արդի խնդիրներից մեկի՝ ֆրուկտոզի բարձր պարունակությամբ սննդակարգերի տոքսիկությանը վերաբերող համաշխարհային գրականության առկա հիմնարար հետազոտությունների տվյալների վրա կատարված ամփոփում է: Հոդվածում լուսաբանվում է պոլիվալենտ օրգանապրոտեկտոր դեղաբուսական հավաքածուի օգտագործման ռացիոնալությունը (նպատակահարմարությունը) կանխարգելիչ և համալիր թերապևտիկ ռազմավարությունների իրագործման ընթացքում: Հայտնի է, որ ֆրուկտոզի երկարատև օգտագործումը բացասաբար է անդրադառնում օրգանիզմի տարբեր օրգանների և համակարգերի ֆունկցիոնալ վիճակի վրա: This article is the result of a review of the world literature devoted to fundamental research of modern medical problems, the toxicity of high fructose containing diets. The article highlights the rationality of the use of the herbal collection submitted as a polyvalent organoprotector and stabilizer in preventive medicine and complex therapeutic strategies. It is known that long-term use of fructose negatively affects the functional state of various organs and systems of the organism. Along with the proven impacts on the cardio-vascular, endocrine, excretory and other systems, recent studies underscore significant neurotoxicity of such diets manifested as impairment in the processes of synaptic plasticity and realized in dysfunction of cognitive, emotional and other types of activity of the brain.
Keywords: Medicine